Forms and Functions of Expressive Speech Act in Javanese - khafidhoh khafidhoh (Ahmad Dahlan Journal of English Studies, 2018)
AbstractThis research aims at investigating the forms and functions of expressive speech act in Javanese. The research method used in this research is descriptive qualitative method so the researcher analyzes the data in this research through description. There are two main results of this research. Firstly, the forms of expressive speech act in Javanese involve literal direct speech acts, literal indirect speech acts, non-literal direct speech act, and non-literal indirect speech acts. Then, the functions of expressive speech act in Javanese involve congratulating, thanking, showing sympathy, asking for apologize, complimenting, criticizing, complaining, and blaming.Â Keywords: speech act, expressive, forms, functions